Quantitative Clinical Pharmacology of T‐Cell Engaging Bispecifics: Current Perspectives and Opportunities - Peter N. Morcos; Junyi Li; Iraj Hosseini; Chi‐Chung Li (Wiley, 2021)
T‐cell directing/engaging bispecifics (TDBs) enable a powerful mode of action by activating T‐cells through the creation of artificial immune synapses. Their pharmacological response involves the dynamic inter‐relationships among T‐cells, tumor cells, and TDBs. This results in complex and challenging issues in understanding pharmacokinetics, tissue distribution, target engagement, and exposure‐response relationship. Dosing strategy plays a crucial role in determining the therapeutic window of TDBs because of the desire to maximize therapeutic efficacy in the context of known mechanism‐related adverse events, such as cytokine release syndrome and neurological adverse events. Such adverse events are commonly reported as the most prominent events during the initial treatment cycles and dissipate over time. Therefore, the kinetic characterization of the inter‐relationships between exposure/target engagement and safety/efficacy outcomes is crucial in designing the optimal dosing regimen to maximize the benefit/risk of TDB agents. In this review, we discuss the key clinical pharmacological considerations in drug discovery and development for TDBs and provide a summary of TDBs currently in clinical development. We also propose forward‐looking perspectives and opportunities to derive insights through quantitative clinical pharmacology approaches.